Investigation of potential Shiga toxin producing Escherichia coli (STEC) associated with a local foodborne outbreak using multidisciplinary approaches - Kristen A. Lozinak; Niketa Jani; Jayanthi Gangiredla; Isha Patel; Christopher A. Elkins; Zonglin Hu; Prince A. Kassim; Robert A. Myers; Pongpan Laksanalamai (Food Science and Human Wellness)
Shiga toxin producing Escherichia coli (STEC) outbreak is a public health concern as it can potentially cause a variety of clinical manifestations including diarrhea, hemorrhagic colitis and hemolytic uremic syndrome (HUS). However E. coli are generally innocuous commensal organisms, and there is a need to discriminate pathogenic from non-pathogenic isolates rapidly and accurately. In this study, we have used standard culture based methods and advanced molecular approaches to characterize E. coli in food in a local outbreak investigation. We show that the application of DNA based detection methods including real-time PCR and DNA microarray along with a traditional culture method can identify the organism implicated in an outbreak at the strain level for pathogenic potential.